Hämodynamische Stabilisierung des septischen Patienten in der Notaufnahme - Schmoch, Thomas; Bernhard, Michael; Siegler, Benedikt Hermann; Brenner, Thorsten; Weigand, Markus A. (Notfall & Rettungsmedizin, 2019)
Sepsis and septic shock are the most serious forms of infection. Being emergencies, they have to be treated adequately and without any delay by rescue and emergency medical services as well as in the emergency department. Thereby, the early and adequate identification of affected patients, a rapid onset of an anti-infective therapy and immediate hemodynamic stabilization are crucial for the outcome. This article provides an overview of the necessary treatment steps that must be started in the emergency department, with a focus on hemodynamic stabilization.
First online: 12 September 2018
Gesehen am 03.09.2019